Evaluation of wound healing potential of Jatropha gossypifolia Linn. root extracts in normal and diabetic rats - Harneet Singh; Surendra Kr. Sharma (International Journal of Phytomedicine, 2013)
Jatropha gossypifolia Linn. is used in Indian folk medicine for treatment of cuts and wounds. Root extract is used to promote wound and fracture healing in animals. Present study was conducted to assess wound healing potential of ointments prepared using successive extracts of roots of the plant. Incision and excision wounds were inflicted upon normal and nicotinamide streptozotocin-induced diabetic rats, respectively. Animals were treated topically with ointments containing 5% and 10% w/w petroleum ether (60-80°C), chloroform, methanol and aqueous extracts. Percentage of wound contraction, epithelization time, tensile strength, hydroxyproline content and histopathology of regenerated skin were evaluated in comparison with reference nitrofurazone (0.2% w/w) ointment. Breaking strength of incision wounds in 5% and 10% w/w methanolic extract ointment treated groups significantly (P < 0.01) increased to 695.75 and 759.50 g, respectively, as compared to standard (653.92g). In diabetic rats, apart from methanol extract, aqueous extract also exhibited extraordinary wound healing capacity and elevated hydroxyproline content. Measurement of hydroxyproline, the product of collagen breakdown, is used as an index of collagen turnover. Elevated hydroxyproline content in diabetic animals signify the increased collagen deposition in wounded tissues as evident from histopathology. There is also an increase in the tensile strength of incision wounds in rats. The experimental study confirms the folk medicinal use of the plant.